The Impact of Flood Disasters on Public Health in Sultan Daulat District Subulussalam City in 2025 - Ricca Nophia Amra; Fitriani Bancin; Rahayu Ningsih; Irma Noviana; Ira Sanjaya (Pascasarjana Universitas Mataram, 2025)
Indonesia is a country prone to flooding, which has wide-ranging impacts on public health, including in Subulussalam City, Aceh Province. This study aims to describe the impact of flooding on community health and the form of post-disaster health service responses in Sultan Daulat Subdistrict in 2025. The study uses a descriptive design with a case study approach based on data from community service activities carried out by lecturers and students of the Medica Bakti Persada Midwifery Academy. Data were obtained from official reports on the number of affected residents and displaced persons, observations of environmental conditions, and documentation of health services provided to 50 affected residents, with a primary focus on pregnant women, toddlers, and the elderly. The results show that the flood led to disrupted access to health services, declining environmental quality, and an increased risk of infectious diseases such as acute respiratory infections, skin diseases, and digestive disorders. Free health services in the form of medical check-ups and simple counseling on personal hygiene, clean water management, and prevention of infectious diseases received a positive response from the community. This activity also demonstrates the strategic role of higher education institutions as partners of local government and as field-based learning centers for students in disaster management. It is concluded that flooding in Sultan Daulat Subdistrict has the potential to cause serious health problems, thus requiring a rapid, well-planned, and sustainable health response, as well as strengthened collaboration between government, health facilities, and higher education institutions in disaster preparedness and management. Further research with more detailed clinical data recording is needed to support evidence-based policy formulation.